The Impact of Transformational Verses Strategic Leadership Styles in the Success of Engineering Teams - SAEED, AHMAD MOHAMMAD (2023)
Engineering teams' success is based on their ability to work effectively and use their skills, experience, and knowledge to achieve results. To achieve this, the team needs robust and effective leadership. The research seeks to identify the elements of each style that can contribute to the success of engineering teams and to investigate the potential effects of each on the team's overall performance. Furthermore, this research will seek to understand the dynamics of the team that are impacted by the leadership style and its effectiveness on the team's performance. Additionally, this research will analyze the relationship between the Transformational and Strategic leadership styles and the team's success and how the two kinds interact to achieve the desired results. Finally, this research will provide recommendations for engineering teams on effectively implementing the leadership style that best suits their goals and objectives. The investigation utilized a quantitative research approach that collected and analyzed numerical data. The research will include workers from several fields. The sample will be selected randomly to generalize the study's results. The minimum required sample size for the analysis will be 100 participants to ensure sufficient statistical power. Data was collected using web-based survey websites. The strategy entailed uploading the questionnaire on the platform and generating a link randomly sent to potential respondents. The instrument contained elimination questions to ensure that only individuals in the UAE engineering sector were allowed to participate. Descriptive statistics were performed to provide a starting point for the research and determine the participant distribution within the target sample. Pearson Moment correlation analysis was performance to evaluate the strength of the relationship between employee engagement and transformational leadership on employee outcomes. The study conducted a linear regression analysis to estimate the impact of the predictor variable on the dependent variable. Besides, ANOVA was performed to determine whether there were significant differences in the participants' demographic characteristics, including work experience, gender, age, and highest educational attainment, concerning the study variables. The findings demonstrated that transformational and strategic leadership significantly influenced organizational performance. Besides, employee engagement was a significant moderator between the independent and dependent variables. Nonetheless, transformational leadership was more appropriate in strengthening the engineering team’s internal competitiveness than strategic leadership. The phenomenon signifies that engineering teams could experience advantages from having a leader who can encourage and stimulate team members to collaborate toward common objectives. The results of this study additionally enhance the expanding knowledge base regarding the influence of various leadership approaches on team productivity.